2017
DOI: 10.3389/fpls.2017.00541
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Treatments Can Induce AcLEAFY COTYLEDON1 Expression and Trigger the Accumulation of Storage Products during Prothallus Development of Adiantum capillus-veneris

Abstract: A seed is an intricate structure. Of the two development processes involved in seed formation, seed maturation, or seed program includes accumulation of storage products, acquisition of desiccation tolerance, and induction of dormancy. Little is known about how these processes were originated and integrated into the life cycle of seed plants. While previous investigation on seed origin was almost exclusively through fossil comparison in paleobotany, a wealth of information about the key role of LEAFY COTYLEDON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…The requirement of LEC1 to regulate maturation processes opens the possibility that LEC1 may have played a critical role in the evolution of the maturation phase and the seed habit. Consistent with this possibility, phylogenetic analysis revealed that LEC1 ‐type genes, which are shared among all spermatophytes, are first detected among basal land plant lineages in lycophytes (Xie et al ; Kirkbride et al ; Cagliari et al ; Fang et al ; Han et al ), suggesting that LEC1 originated at least 30 million years before the appearance of seed plants in the fossil record. Based on their expression patterns, LEC1 orthologs have been suggested to play roles in promoting desiccation tolerance and lipid accumulation in Selaginella (lycophyte) species and storage macromolecule accumulation in reproductive organs of the fern, Adiantumcapillus‐veneris (Xie et al ; Kirkbride et al ; Fang et al ; Han et al ).…”
Section: Lec1 Is a Key Regulator Of The Maturation Phasementioning
confidence: 85%
“…The requirement of LEC1 to regulate maturation processes opens the possibility that LEC1 may have played a critical role in the evolution of the maturation phase and the seed habit. Consistent with this possibility, phylogenetic analysis revealed that LEC1 ‐type genes, which are shared among all spermatophytes, are first detected among basal land plant lineages in lycophytes (Xie et al ; Kirkbride et al ; Cagliari et al ; Fang et al ; Han et al ), suggesting that LEC1 originated at least 30 million years before the appearance of seed plants in the fossil record. Based on their expression patterns, LEC1 orthologs have been suggested to play roles in promoting desiccation tolerance and lipid accumulation in Selaginella (lycophyte) species and storage macromolecule accumulation in reproductive organs of the fern, Adiantumcapillus‐veneris (Xie et al ; Kirkbride et al ; Fang et al ; Han et al ).…”
Section: Lec1 Is a Key Regulator Of The Maturation Phasementioning
confidence: 85%
“…While no LEC1 -like sequences were found the genomes of algae and bryophytes, LEC1 -like sequences were present in the lycophyte Selaginella (highlighted in Figure 5A ), as well as in other lycophyte and fern genomes ( Xie et al, 2008 ). Gene expression and genetic complementation analyses excluded the possibility that the LEC1 -like sequences identified in the pteridophytes are pseudogenes ( Figure 5B ) and demonstrated that the LEC1 -like sequences are expressed under stress conditions ( Figure 5C ; Fang et al, 2017 ; Li et al, 2017 ).…”
Section: Lec1 -Like Sequences Emerged From Pteridophytes And...mentioning
confidence: 99%
“…Not only could its gametophytic development be manipulated under laboratory conditions, but its representative gene expression and metabolite accumulation were also possible to analyze during gametophytic development. Using such an experimental system, Fang et al (2017) showed that sugar treatments can induce Adiantum capillus-veneris LEAFY COTYLEDON1 ( AcLEC1 ) expression and trigger the accumulation of storage products during prothallus (gametophyte) development. While it remains to be determined whether the sugar treatments directly caused the increase in AcLEC1 expression and the accumulation of storage products, these findings provided the first supporting evidence for the golden-trio hypothesis.…”
Section: Preliminary Testing Of the Golden-trio Hypothesismentioning
confidence: 99%
See 1 more Smart Citation